Abel Gance po trzykroć oskarża: metafizyka i apokaliptyczna wyobraźnia w służbie pacyfizmu - Kłys , Tomasz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This text is inspired by monumental and editorially perfect BluRay/DVD box set J’accuse (Gaumont, Paris 2017). It includes BluRay and DVD editions of all three J’accuse films (1919, 1937, 1956), two other Gance’s films, specifying the context of „trilogy” (Les Gaz mortels, 1916 and La Fin du monde, 1931) and the large director’s monography by Laurent Véray. From this revelatory archive emerges the image of Abel Gance as an artist who for 40 years of his filmmaker’s career was incessantly reworking deep trauma caused by World War One. It resulted in three J’accuse films, two other finished films and some other never realized screenplays and projects which made up particular work-in-progress whose mission is a message of peace. The text analyzes all three versions of J’accuse, concentrating on their allegorical style, metaphysical concept of ressurrection of fallen soldiers and apocalyptic vision of resurrected dead men’s processions which by its horror should persuade the mankind to stop all wars. In the last J’accuse (1956) – in fact, strongly shortened and reedited film from 1937 – Gance used the technique of triptych in which the picture was projected by three parallelly set projectors on the large screen with proportions 4:1. This version, immersing perceptually and sensorically spectator in the wide-format picture full of war horrors, today seems to be much more effective medium for message of peace than undecided between pacifism and patriotism, impressionistic in its style film from 1919, or laden with full of pathos verbal rhetorics J’accuse 1937.